2023
DOI: 10.3390/foods12030470
|View full text |Cite
|
Sign up to set email alerts
|

SVM Regression to Assess Meat Characteristics of Bísaro Pig Loins Using NIRS Methodology

Abstract: This study evaluates the ability of the near infrared reflectance spectroscopy (NIRS) to estimate the aW, protein, moisture, ash, fat, collagen, texture, pigments, and WHC in the Longissimus thoracis et lumborum (LTL) of Bísaro pig. Samples (n = 40) of the LTL muscle were minced and scanned in an FT-NIR MasterTM N500 (BÜCHI) over a NIR spectral range of 4000–10,000 cm−1 with a resolution of 4 cm−1. The PLS and SVM regression models were developed using the spectra’s math treatment, DV1, DV2, MSC, SNV, and SMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Internal validation is a commonly used method for evaluating models free of experimental and environmental conditions’ limitations ( Luo et al, 2020 ; Vasconcelos et al, 2023 ). In this study, we used 10-fold cross validation to conduct internal validation.…”
Section: Resultsmentioning
confidence: 99%
“…Internal validation is a commonly used method for evaluating models free of experimental and environmental conditions’ limitations ( Luo et al, 2020 ; Vasconcelos et al, 2023 ). In this study, we used 10-fold cross validation to conduct internal validation.…”
Section: Resultsmentioning
confidence: 99%
“…55 Similar findings were made by another researcher, who concluded that SVMR outperformed PLSR in prediction performance. 45,46,55,56 In this study, the best prediction performance values are provided by MLPR, a nonparametric regression. Applying a nonparametric regression model based on a local polynomial estimator outperforms a mathematical computation technique, including the support vector machine approach.…”
Section: Tss Valuementioning
confidence: 99%
“…Chewiness determines the number of chews required for the meat to be ready for swallowing, and juiciness is dependent on the protein structures/compositions of the muscle fibers and connective tissues and is correlated to the sensation of moisture observed in the initial chewing movements [44,47,48]. It was possible to verify that the intramuscular composition and fat deposition existing in the dry-cured Bísaro loin lines [22,26] resulted in the rapid release of fluid contained in them, justifying the variation found in the texture parameters of our work. All of them showed a relatively large range (6.56-2.44; 5.44-2.13; 6.11-3.44 for hardness, chewiness and juiciness, respectively) with average values of 3.90, 3.62 and 5.10, respectively, and standard deviations of 1.23, 0.85 and 0.64, respectively.…”
Section: Sensory Datamentioning
confidence: 99%
“…Regarding appearance, mean values for fat color and color were lower (3.11 and 4.05, respectively) than those described by Revilla et al [49] and were within those obtained by Seong et al [53], with a value of 4.75 given by tasters for loins ripened for 60 days in their study. The color of meat is closely associated with freshness, myoglobin content and technological quality traits such as pH or water-holding capacity, which, in Bísaro pork meat, indicate significant variations in color and tenderness [22,26,45]. These indicators play a crucial role in visual attraction and sensory acceptability and are directly related to financial losses for the industry if they do not meet consumer demands [11,13].…”
Section: Sensory Datamentioning
confidence: 99%
See 1 more Smart Citation